Medication adherence among ambulatory patients with type 2 diabetes in a tertiary healthcare setting in Southwestern Nigeria - Adisa R; Fakeye TO; Fasanmade A (Centro de Investigaciones y Publicaciones Farmaceuticas, 2011)
Objective: To assess adherence to medication among ambulatory patients with type 2 diabetes, ascertain the level of glycemic control, and evaluate patients' opinions on probable reasons for non-adherence with a view to identify areas of intervention to improve adherence.Methods: A prospective cross-sectional study was carried out at a 900-bed tertiary teaching hospital in Ibadan, Southwestern Nigeria between June and August, 2009. Out of 140 consented patients, 114 (81.4%) properly responded to the validated and pre-tested data collection tool and these were subsequently considered for analysis. Descriptive statistics were used to summarize the data. Means and proportions were compared using student t-test and chi-square or Kruskal-Wallis test as appropriate, with p<0.05 considered statistical significant.Results: Approximately sixty percent of the patients were adjudged adherent with prescribed medication. Out of 58.8% of the cohort who gave their recent fasting plasma glucose (FPG) values, 59.7% had FPG above 110mg/dL. The mean FPG for patients was 139.05 (SD=70.5)mg/dL, males and females significantly differed in their mean FPG, 146.55 (SD=85.0)mg/dL versus 133.33 (SD=57.6)mg/dL respectively (p=0.032). Also, the mean FPG values for adherent patients, 137.09 (SD=59.3)mg/dL was lower than their non-adherent counterparts, 143.92 (SD=87.6) mg/dL, but the difference was not statistically significant (p=0.095). Financial constraint (34.4%) was the major barrier to optimal adherence with medication. A significant association exist between genders and opinions on physician's mode of approach during patient-physician interaction as a contributory factor for non-adherence (p=0.038).Conclusion: Medication adherence of ambulatory type 2 diabetes patients is considerable. However, the relatively high level of adherence did not appear to have significantly impacted on patients' glycemic status due to a substantial number who had plasma glucose above the recommended targets. Multiple methods may be required to detect patient who report adherence but who may in fact be non-adherent. Also, adherence to other aspects of diabetes management plan needs to be encouraged in order to accomplish optimal glycemic control. Initiatives targeting patient-specific intervention to improve medication adherence should be considered.